The Analysis Of The Effect Of Population, Open Unemployment Rate, And Poverty As The Quality Of Human Resources In Bangkalan Regency - Siti Charimah; Ririt Iriani Sri Setiawati (UNIVED Press, 2024)
This research aims to analyze the influence of population size, open unemployment rate, and poverty on the quality of human resources as measured by the human development index indicator. The Central Statistics Agency provides secondary data for the period 2010-2022. Multiple linear regression analysis is the method used in this research with the help of the SPSS program. Based on research results, population size and poverty have a significant effect on the quality of human resources in Bangkalan Regency. Meanwhile, the open unemployment rate has no significant effect on the quality of human resources in Bangkalan Regency.